2003
DOI: 10.1002/gps.839
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial impairment in dementia with Lewy bodies and Alzheimer's disease: a process analysis approach

Abstract: Subjects with DLB and psychosis have more severe visual-perception (VH errors) impairments than subjects with DLB and predominant parkinsonian features, and AD subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 20 publications
3
32
3
Order By: Relevance
“…61,64,66,73,77,81 Of note, results showing overall equivalent visuospatial performance between groups have indicated greater DLB-associated executive errors (eg, planning/organization) on qualitative analysis. 67,71 Such findings are consistent with the relative paucity of LBs in parietal and especially occipital cortex, but a catastrophic loss of cholinergic and dopaminergic pathways to these regions because of a massive preponderance of LB pathology in downstream brainstem regions. 50…”
Section: Dlbsupporting
confidence: 80%
“…61,64,66,73,77,81 Of note, results showing overall equivalent visuospatial performance between groups have indicated greater DLB-associated executive errors (eg, planning/organization) on qualitative analysis. 67,71 Such findings are consistent with the relative paucity of LBs in parietal and especially occipital cortex, but a catastrophic loss of cholinergic and dopaminergic pathways to these regions because of a massive preponderance of LB pathology in downstream brainstem regions. 50…”
Section: Dlbsupporting
confidence: 80%
“…Numerous studies have observed greater impairments in DLB compared to AD on visuospatial and constructional tasks (Collerton et al 2003;Hansen et al 1990;Noe et al 2004;Simard et al 2003). Even brief screening tasks, such as pentagon-copying from the Mini Mental Status Examination (MMSE; Folstein et al 2001) have been reported to reveal greater impairment in DLB (Ala et al 2001) or DLB and PDD (Cormack et al 2004a) compared to AD.…”
Section: Visuoperceptual and Spatial Functionsmentioning
confidence: 96%
“…Both DLB and PDD show relatively preserved memory performance compared to AD subjects on the Dementia Rating Scale (Aarsland et al 2003b). Patients with AD generally also perform more poorly than DLB on the immediate and delayed recall portions of tests of word list learning such as the Selective Reminding Test (SRT; Noe et al 2004) and the California Verbal Learning Test (CVLT; Simard et al 2002), though one study found DLB to perform better than AD only on the recognition part of the CVLT (Hamilton et al 2004), perhaps because some of the DLB subjects in that study may actually have had the Lewy body variant of AD. As on list learning, DLB subjects may show better prose passage (WMS-R Logical Memory) immediate and delayed recall than AD (Calderon et al 2001).…”
Section: Memorymentioning
confidence: 98%
“…40 Barnes and David 41 compared visual imagery, visual perception, and recognition memory in nondemented PD patients with and without hallucinations and found that PD patients with visual hallucinations were more impaired in object perception. In the present study, hallucinating DLB/ PDD patients were more impaired in all visual scores compared to patients without hallucinations.…”
Section: Figure (A Through C) Mean and 95% CI Of The Discrimination mentioning
confidence: 99%